Pengembangan E-Book Interaktif Anti Korupsi Melalui Kegiatan P5 Pada Siswa Sekolah Dasar - Dzikraa Febry Fauzie; Komariah Komariah; Yayang Furi Furnamasari (Pusat Riset dan Inovasi Nasional, 2023)
This research is motivated by the problem of corruption, which is currently still the main cause of obstruction of national development. Anti-corruption education as a preventive form of corruption eradication is attempted to build anti-corruption attitudes and understanding of students. Indications that students are infected with corruption are characterized by lying to get benefits and lack of discipline. Seeing the challenges in order to improve the character of students, the P5 program was formed, namely the profile project of strengthening Pancasila students in the independent curriculum. Thus, this research aims to create an interactive learning media in the form of an E-Book with the title